On exact values of quasiwidths of some classes of functions - Vakarchuk, S. B.; Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
In the Hilbert space L 2(Δ2), Δ = [0, 2 π] we establish exact estimates of the Kolmogorov quasiwidths of some classes of periodic functions of two variables whose averaged modules of smoothness of mixed derivatives are majorizable by given functions.